And the ship sails on [videorecording (DVD)] - Fellini, Federico; Jones, Freddie, 1927-2019; Jefford, Barbara, 1930-2020-; Poletti, Victor; Bausch, Pina (Criterion collection, 1999)
In 1914, a colorful melange of celebrities embark on a funeral voyage for a dead opera star. An allegorical film blending spectacle, humour, poignance and grotesquerie.